Gambaran Kelengkapan Pendokumentasian Catatan Perkembangan Pasien Terintegrasi (CPPT) oleh Perawat - Enabella, Anindi Tri; Lestari, Aurelia; Noviana Elika, Yolanda; Ayu Florensa, Maria Veronika; Kasenda, Edson (Jurnal Perawat Indonesia, 2024)
Background: Cyberbullying is bullying conducted through social media. It’s usually experienced by early adults (18-25 years old) who are active in using the internet. Cyberbullying can change their well-being, specially psychological well-being. The aims of study is to identify relationship between cyberbullying and psychological well-being in early adults in Tangerang Regency. Methodology: This quantitative study used cross-sectional approach. The sample was calculated using Slovin formula and obtained 217 respondents which use convenience sampling technique. This study used two instruments which is Cyberbullying and Online Aggression Survey Instrument and Psychological Well-being Scale questionnaires. The instruments in the study used valid and reliable Cyberbullying and Online Aggression Survey Instrument and Psychological Well-being Scale questionnaires. Data collection was carried out from February 2023 to April 2023 using an online questionnaire. The data obtained were analyzed using univariate analysis and bivariate analysis with the Gamma correlation statistical test. The results showed that the level of cyber bullying in early adults in Tangerang Regency was in the low category 64.5%, medium 29.5% and high 6%, then the level of psychological well-being was in the low category 28.6%, medium 22.1% and high 49.3%. There is a significant relationship (p<0.001) between cyberbullying and psychological well-being in early adulthood in Tangerang Regency. Suggestion: Collaboration between nurse educators and community nurses utilizing technological advances and social media is needed to increase socialization about cyberbullying prevention and management for victims that are easily accessible to the community. Support from the government is needed so that this health promotion innovation can reach all regions in Indonesia.   Keywords: Cyberbullying, psychological well-being, early adulthood.